Investigation of causative genetic defects in patients with primary immunodeficiency by next generation sequencing (Annals of Medical Research, 2021)
Aim: Inborn errors of immunity are rare diseases presented with a broad range of clinical symptoms. There are more than 450 causative genetic defects and the genetic diagnosis is very important for the patients. Use of next generation sequencing facilitated the molecular and genetic identification of these diseases for last 10 years. We aimed to search disease-causing defects in patients with primary immunodeficiencies (PIDs) by next generation sequencing. Materials and Methods: The study included 12 PID patients without genetic diagnosis. We performed whole exome sequencing for the investigation of genetic defects and Sanger sequencing for variant validation.Results: We found seven different disease-causing mutations in 6 patients with a diagnosis rate of 50%. There were three known pathogenic variants in CYBA, SBDS and RAG2 genes. We identified two additional new causative variants in NCF2 and SBDS genes and two novel mutations in PGM3 and SAMD9L genes.Conclusion: The result revealed that NGS-based methods especially whole exome sequencing can be used efficiently for genetic diagnosis of primary immunodeficiency diseases.
Keywords: Genetic diagnosis; next generation sequencing; primary immune deficiencies